下列运算正确的是 ( )
A. 4 = ± 2 B. ( 1 2 ) - 1 = - 2
C. ( - 3 a ) 3 = - 9 a 3 D. a 6 ÷ a 3 = a 3 ( a ≠ 0 )
下列计算正确的是 ( )
A. 3 a − 2 a = a B. 2 + 5 = 7 C. ( 2 a ) 3 = 2 a 3 D. a 6 ÷ a 3 = a 2
A. a 2 · a 2 = 2 a 2 B. a 2 + a 2 = a 4 C. ( a 3 ) 2 = a 6 D. a 8 ÷ a 2 = a 4
A. 2 a 5 − 3 a 5 = a 5 B. a 2 · a 3 = a 6 C. a 7 ÷ a 5 = a 2 D. ( a 2 b ) 3 = a 5 b 3
A. x 2 + x 2 = x 4 B. x 3 · x 2 = x 6 C. 2 x 4 ÷ x 2 = 2 x 2 D. ( 3 x ) 2 = 6 x 2
A. ( a 3 ) 2 = a 5 B. a 2 · a 3 = a 5 C. a 6 ÷ a 2 = a 3 D. 3 a 2 − 2 a 2 = 1
A. a ( a + 1 ) = a 2 + 1 B. ( a 2 ) 3 = a 5
C. 3 a 2 + a = 4 a 3 D. a 5 ÷ a 2 = a 3
A. a 3 + a 3 = 2 a 3 B. a 3 · a 2 = a 6
C. a 6 ÷ a 2 = a 3 D. ( a 3 ) 2 = a 5
A. a 2 + a 3 = a 5 B. a 2 · a 3 = a 5 C. a 3 ÷ a 2 = a 5 D. ( a 2 ) 3 = a 5
A. a 2 · a 3 = a 6 B. a 6 ÷ a - 2 = a - 3
C. ( - 2 a b 2 ) 3 = - 8 a 3 b 6 D. ( 2 a + b ) 2 = 4 a 2 + b 2
A. x 2 · x 3 = x 6 B. x 6 ÷ x 3 = x 3 C. x 3 + x 3 = 2 x 6 D. ( - 2 x ) 3 = - 6 x 3
A. 3 a 2 − a 2 = 3 B. ( a 2 ) 3 = a 6
C. a 2 · a 3 = a 6 D. a 6 ÷ a 2 = a 3
A. a 8 ÷ a 4 = a 2 B. ( 2 a 2 ) 3 = 6 a 6
C. 3 a 3 − 2 a 2 = a D. 3 a ( 1 − a ) = 3 a − 3 a 2
A. a 5 + a 5 = a 10 B. a 7 ÷ a = a 6
C. a 3 · a 2 = a 6 D. ( − a 3 ) 2 = − a 6
A. 2 m 3 + 3 m 2 = 5 m 5 B. m 3 ÷ m 2 = m
C. m ⋅ ( m 2 ) 3 = m 6 D. ( m − n ) ( n − m ) = n 2 − m 2